Signal Processing Techniques for Advanced Communication Systems: A Review of Innovations and Challenges - Sharma, Shobhit (Journal of Advanced Research in Electrical Engineering and Technology, 2025)
Signal processing has played a transformative role in the evolution of modern communication systems, enabling more efficient and reliable transmission, reception, and analysis of vast amounts of data. With the rapid advancements in communication technologies, particularly in 5G, 6G, and the Internet of Things (IoT), signal processing techniques have become even more critical. This review explores the latest innovations in signal processing, focusing on key technologies such as multiple-input multiple-output (MIMO), adaptive filtering, wavelet transforms, and other advanced modulation and coding techniques that are essential for achieving high data rates, low latency, and robust performance in these next-generation systems. Additionally, the article highlights several challenges faced by the industry, including spectrum scarcity, energy consumption, hardware limitations, and interference management. It delves into the role of signal processing in emerging areas like cognitive radio, satellite communication, and wireless communication systems, providing real-world applications and case studies. Furthermore, the review looks at future directions for the field, particularly the integration of machine learning techniques to optimize signal processing tasks and the potential for quantum signal processing to revolutionize the way communication systems process information. By addressing both current innovations and ongoing challenges, this review offers a comprehensive perspective on the future of signal processing in advanced communication systems, underscoring the importance of interdisciplinary research and technological integration in shaping the next generation of communication technologies.